Characteristics of Wound Assessment According to Meggit-Wagner and Pedis and Spiritual Response in Diabetic Ulcer Patients at RSUD Dr. Soekardjo Tasikmalaya City - Bayu Brahmantia; Yuyun Solihatin; Heri Budiawan (INDOGENIUS, 2025)
Background & Objective: Diabetic ulcer is one of the complications of diabetes mellitus. Assessment of diabetic ulcers is done as a basis for determining wound care and therapy. Meggit-Wagner and Pedis have the advantages of a simple, easy-to-remember system, based on the location and depth of ulceration. A good quality of life for ulcer patients is an optimal functional condition in terms of physical, psychological, environmental, social and spiritual aspects.  Good spirituality and social can improve the health of diabetic ulcer patients. Method: The purpose of the study was to determine the wound with Meggit-Wagner and PEDIS assessment and the spirituality of diabetic ulcer patients. Descriptive case study research method, sample of 3 respondents.   Result: The results showed that the respondents' education level was high school / vocational school, the gender of the respondents was female, the results of the Maggit-Wagner wound assessment of the wound condition of respondents 1, 2 and 3 grade 3, namely deep wounds with cellulitis or abscess formation. Conclusion: The results of the PEDIS assessment of respondents 1, 2 and 3 grade 3 wounds, namely severe infection based on PEDIS characteristics, are characterized by more than two signs in the characteristics: cellulitis >2 cm, abscesses in deep tissue and gangrene but no systemic inflammation. It is suggested that nurses can apply Maggit-Wagner and PEDIS wound assessment so that they are more precise in providing dressings and better understand the condition and characteristics of the wound.